2021
DOI: 10.3390/nu13082543
|View full text |Cite
|
Sign up to set email alerts
|

One-Week High-Dose β-Alanine Loading Improves World Tour Cyclists’ Time-Trial Performance

Abstract: Supplementation with β-alanine is becoming a common practice in high-performance athletes. The purpose of the present study was to investigate the effects of a one-week high-dose β-alanine loading phase employing a sustained-release powder on preserving the time-trial performance capacity of world tour cyclists during overreaching training. Per day, 20 g of sustained-release β-alanine was administered during one week (7 days) of intensive team training camp in a randomised balanced placebo-controlled parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In addition, the sample size was calculated based on the mean power in the first 8-min TT, which served as the main outcome of the study. Considering a SD of the mean power of 12.3 W reported in a similar population (Ávila-Gandía et al, 2021), a precision of 9 W with an alpha risk of 5%, and a statistical power of 80%, 23 participants are required. Accounting for a potential 25% loss to follow-up, a total of 29 cyclists were recruited.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sample size was calculated based on the mean power in the first 8-min TT, which served as the main outcome of the study. Considering a SD of the mean power of 12.3 W reported in a similar population (Ávila-Gandía et al, 2021), a precision of 9 W with an alpha risk of 5%, and a statistical power of 80%, 23 participants are required. Accounting for a potential 25% loss to follow-up, a total of 29 cyclists were recruited.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the high daily dose of β-alanine of 15 g for a total intake of 450 g during the study period, and secondly, the rate of paresthesia in subjects treated with the active product as compared with placebo. In relation to the dose of β-alanine, in a previous study of our group, 20 g of the same sustained-released formulation was administered during one week (7 days) as a short-term strategy to maintain high-intensity cycling performance ( 15 ). In that study, β-alanine supplementation was scheduled in 4 daily intakes and no side effects or paresthesia were reported.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in healthy volunteers, de Salazar et al (14) reported that 8 g in a single oral dose of an innovative sustained-release β-alanine formulation (BETAFOR3MAX ® ) provided more efficient release kinetics with a 2-fold increase in bioavailability compared to the group that did not take the product without a significant increase in paresthesia. This dose has been the highest acute dose reported in a single administration, higher than the standard recommended daily dose of 6.4 g. In another study of Ávila-Gandía et al (15), the administration of 5 g of this same formulation, four times daily during 1 week to world tour cyclists during overreaching training, helped to attenuate 10-min time trial performance losses with no side effects or paresthesia. Moreover, there are other variables that may exhibit changes after the ingestion of a high dose of β-alanine.…”
Section: Introductionmentioning
confidence: 91%